Konsep Islam tentang Ilmu Pengetahuan dan Sains - Yosse Amanda Pratama; Dede Rubai Misbahul Alam; Shonhaji Jaoharul Huda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The Islamic conception of science views knowledge as a unity originating from Allah SWT and directed towards realizing human welfare. Islamic science does not separate the rational, empirical, and spiritual dimensions, but rather integrates revelation, reason, and sensory experience in obtaining truth. Science from an Islamic perspective is understood as a human effort to read and understand the verses of kauniyah as a manifestation of God's power in the universe. This study aims to analyze the Islamic conception of science and its relationship with science, and examine the urgency of integrating the two in facing the challenges of modern science. The research method applied in this study is a literature study with a qualitative approach, through descriptive and interpretive analysis of various relevant literature sources. The research findings indicate that the integration between Islamic science and science plays a strategic role in overcoming the scientific dichotomy, strengthening the ethical foundation of science, and building a scientific paradigm oriented towards the values ​​of monotheism and humanity. Thus, the Islamic conception of science and science offers an alternative, holistic and sustainable scientific framework.